Optimizing in vitro surface sterilization of Cyathea latebrosa spore - Nurul Nadhirah,; Haja Maideen,; Zuraida Ab Rahman,; Ayu Nazreena Othman, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Cyathea latebrosa is one of the lowland tree fern species found in Peninsular Malaysia. This fern species is highly demanded in ornamental landscaping. The in vitro cultures are an important tool for propagation which may contribute toward the reduction of over-exploitation. To overcome these problems, an effective spore surface disinfection protocol is crucial to allow the germination stage to be carried out. This studied had carried out three types of methods which are the packet method (PM), centrifuged method (CM), and soak method (SM) with difference percent of concentration (0, 0.1, 0.5, 1.0, 10 & 30) Mercury Chloride (HgCl2) and Sodium hypochlorite (NaOCl). In contrast, the method and concentration of disinfection affect germination. Our results showed that the soak method in both types of disinfection is a significant difference due to statistical analysis (MANOVA) which gives a positive effect on the germination of the spore. This method is efficient for sterilizing which spore loss is kept to a minimum and has a higher rate of germination (HgCl2-90% & NaOCl-80%). The optimum concentration of HgCl2 was 0.1%, then followed by 0.5% and 1.0%, while for NaOCl was 30%, 20%, and 10%.